Asymmetric supercapacitors based on nickel decorated graphene and porous graphene electrodes. (20th August 2022) - Morenghi, Alberto; Scaravonati, Silvio; Magnani, Giacomo; Sidoli, Michele; Aversa, Lucrezia; Verucchi, Roberto; Bertoni, Giovanni; Riccò, Mauro; Pontiroli, Daniele
Abstract: Thermal exfoliation of graphite oxide is a scalable way to produce macroscopic amount of defective graphene-based compounds with high specific surface area, ideal as electrode materials in high-performance electrochemical supercapacitors. In order to increase the stored energy, defective graphene has been decorated with Ni nanoparticles without exposing the system to air. During the first charge cycle in an aqueous electrolyte (KOH 3.5 M), Ni anchored to graphene proved to easily convert to Ni(OH)2 at the nanoscale and hence to reversibly assume Ni 2+ and Ni 3+ valence during cyclic voltammetry, through its conversion to NiOOH. Such reversible faradaic mechanism led to a one order of magnitude increase of the specific capacitance of electrodes, reaching up to 1900 F/g at 2 mV/s in KOH 3.5 M. An asymmetric supercapacitor was obtained by coupling a pure graphene negative electrode with a Ni decorated graphene positive one. The supercapacitor, operating with aqueous electrolyte, was successfully cycled in the 0–1.5 V voltage range, reaching a maximum specific energy of 37 Wh/kg and a maximum specific power of 5 kW/kg. The devices displayed good reversibility and retained 72% of the specific energy over 10 thousand of cycles. Such promising results disclose to possible industrial implementation of graphene-based supercapacitors, for a wide range of energetic application. Graphical abstract: Image, graphical abstract